Analiza wielkości obrotu towarami rolno-żywnościowymi przed wstąpieniem i po wstąpieniu Polski do Unii Europejskiej - Kondratowicz-Pozorska, Jolanta (The Analysis of Turnover Size of Rural-Food Products Before and after the Accession of Poland to the European Union, 2005)
The paper presents the answers to the following questions:1. Can we hold the current grow tend in Polish export.2. Can we defeat the competitors.3. What changes will we have after the accession.The author has also made a large analysis of empiric material related to export of rural-food products in 1993-2003. Changes of dynamic growth of researched occurrence are presented based on the research results. Prognosis of probable directions of change in dimension of Polish products export in the nearest years is discussed in details.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 462-467